Food acquisition and intra-household consumption patterns: a study of low and middle income urban households in Delhi, India - ., MR Pradhan; Taylor, F C; Agrawal, S; Prabhakaran, D; Ebrahim, S (Indian Journal of Community Health, 2013)
Background: Food habits and choices in India are shifting due to many factors: changing food markets, fast urbanization, food price inflation, uncertain food production and unequal distribution during the past decade. This study aims to explore food acquisition and intra-household consumption patterns in urban low and middle income (LMI) households in Delhi. Methods: Twenty households were randomly selected from the Center for Cardio-metabolic Risk Reduction in South Asia (CARRS) surveillance study. Data were derived from 20 questionnaires administered to women responsible for food preparation, four key-informant-interviews, and 20 in-depth interviews with household heads during September-November 2011. STATA and ATLAS.ti software were used for data analysis. Results: Half of the households spent at least two-thirds of their income on food. The major expenditures were on vegetables (22% of total food expenditure), milk and milk products (16%), and cereal and related products (15%). Income, food prices, food preferences, and seasonal variation influenced food expenditure. Adults usually ate two to three times a day while children ate more frequently. Eating sequence was based on the work pattern within the household and cultural beliefs. Contrary to previous evidence, there was no gender bias in intra-household food distribution. Women considered food acquisition, preparation and distribution part of their self-worth and played a major role in food related issues in the household. Conclusion: Women’s key roles in food acquisition, preparation and intra household food consumption should be considered in formulating food policies and programs.